Pull the Plug or Take the Plunge: Multiple Opportunities and the Speed of Venturing Decisions in the Australian Mining Industry - Bakker, Rene M.; Shepherd, Dean A. (Academy of Management Journal, 2017)
Effectively capturing opportunities requires rapid decision making. We investigate the speed of opportunity-evaluation decisions by focusing on firms’ venture termination and venture advancement decisions. Experience, standard operating procedures, and confidence allow firms to make opportunity-evaluation decisions faster; we propose that a firm’s attentional orientation, as reflected in its project portfolio, limits the number of domains in which these speed-enhancing mechanisms can be developed. Hence, firms’ decision speed is likely to vary between different types of decisions. Using unique data on 3,269 mineral exploration ventures in the Australian mining industry, we find that firms with a higher degree of attention toward earlier-stage exploration activities are quicker to abandon potential opportunities in early development but slower to do so later, and that such firms are also slower to advance on potential opportunities at all stages compared to firms that focus their attention differently. Market dynamism moderates these relationships, but only with regard to initial evaluation decisions. Our study extends research on decision speed by showing that firms are not necessarily fast or slow regarding all the decisions they make, and by offering an opportunity-evaluation framework that recognizes that decision makers can—in fact, often do—pursue multiple potential opportunities simultaneously.